2021
DOI: 10.1039/d1cc01401c
|View full text |Cite
|
Sign up to set email alerts
|

Diverse reactivity of carbenes and silylenes towards fluoropyridines

Abstract: The reaction of IDipp with C5F5N led to functionalization of all three carbon atoms of the imidazole ring with HF2-as the counter-anion (1). Reactivity with 2,3,5,6-tetrafluoropyridine gives only C−F bond...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…However, even after repeated attempts, we were unable to stop this hydrolysis and hence, could not characterize 5a spectroscopically. The CF 3 group of the triflate moiety in 5b resonates at −78.6 ppm in the 19 F NMR, which is slightly different from the resonances of triflates bound to the boron atom (−76.7 ppm in 4) and is characteristic of the free triflate anion.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…However, even after repeated attempts, we were unable to stop this hydrolysis and hence, could not characterize 5a spectroscopically. The CF 3 group of the triflate moiety in 5b resonates at −78.6 ppm in the 19 F NMR, which is slightly different from the resonances of triflates bound to the boron atom (−76.7 ppm in 4) and is characteristic of the free triflate anion.…”
Section: Resultsmentioning
confidence: 85%
“…Clearly, the extension of unexplored carbenes in NHC•borane chemistry is desirable, as it may lead to the discovery of a range of interesting new applications. Due to our current interest in 5-SIDipp [17][18][19], we have prepared here haloboranes 5SIDipp•BHCl 2 , 1 and 5SIDipp•BPhCl 2 , 2 and studied their substitution reactions with AgOTf, AgNO 3 , and water. Furthermore, we have shown that the combination 5-SIDipp and B(C 6 F 5 ) 3 led to the activation of THF and diethyl ether via frustrated Lewis pair (FLP) way.…”
Section: Introductionmentioning
confidence: 99%
“…The smooth formation of 5 and 6 encouraged us to exploit the fluoride affinity of the silicon atoms in the hypersilyl moiety. In line with our current interest in C–F bond activation of perfluoroarenes, we assume that the reactions of 3 or 4 with perfluoroarene might cleave the C–F bond of the fluoroarene and generate organo-germanium or tin compounds along with the elimination of (Me 3 Si) 3 SiF. Alternatively, the tetrylene center can undergo oxidative addition .…”
Section: Resultsmentioning
confidence: 88%
“…Sen group also theoretically calculated the ▵G for the triple C−F activation and characterized the complex by single X‐ray spectroscopy (Scheme 36). [82] …”
Section: C−f Bond Activation By N‐heterocyclic Carbene and Their Isoe...mentioning
confidence: 99%